Andean Landscape Legacies: Comprehensive Remote Sensing Mapping and GIS Analysis of Long-Term Settlement and Land Use for Sustainable Futures (NW Argentina) - Lazzari, Marisa (2024)
Fil: Lazzari, Marisa. University of Exeter. Department of Archaeology and History; Reino Unido